On the state of public health and healthcare Siberian Federal District during the pandemic (some results of 2020) - V. M. Chernyshev; M. I. Voevoda; O. V. Strelchenko; L. S. Shalygina; I. F. Mingazov (Сибирский научный медицинский журнал, 2021)
Introduction. The COVID-19 pandemic has become a huge challenge for the entire healthcare system, medical institutions and doctors. The results of the industry’s activities turned out to be insufficiently effective, and therefore it is necessary to analyze not only what is directly related to the coronavirus infection, but also the consequences that the pandemic has led to. Goal. To analyze the results and consequences of health care activities and the health status of the population of the Siberian Federal District during the COVID-19 pandemic. Material and methods. The statistical data of the Ministry of Health of the Russian Federation, Rosstat, the Central Research Institute for the Organization and Informatization of Healthcare (TSNIIOIS), the Federal Service for Supervision of Consumer Rights Protection and Human Well-Being, as well as data for the Siberian Federal District were used. Scientific publications on the problem under consideration have been studied. Results and discussion. In connection with the beginning of the COVID-19 pandemic in Russia, as in all countries of the world, serious anti-epidemic measures were carried out, the procedure for providing medical care to the population changed, the consequences of which did not have the best effect on their health, including in the Siberian Federal District. The number of visits per resident of the district as a whole decreased by 16.2 %, in the polyclinic by 19.5 %, at home increased by 44.4 %. The number of visits for preventive purposes decreased by 6 %, and the coverage of dispensary observation by 11.2 %. The proportion of patients with oncological diseases in stages 3-4 increased to 40.6 %. Hospitalization of the SFO declined by 17.2 %, the number of operated patients 17.8 %, and postoperative complications have increased by 43.7 % from 1.07 to 1.54 %. Total mortality amounted to in 2020 for 14.5 per 1,000 population, i.e. increased by 18 % compared to 2019 year, while only 1/3 was due to COVID-19. In 2020, the number of Russians decreased by 510 thousand people. Conclusions. The results of health care activities, a significant deterioration in the health of the population and the complication of the demographic situation in the country during the pandemic, indicate serious shortcomings in the organization of medical care to the population, primarily in extreme situations, and requires a deep analysis and adequate measures to improve the structure and functioning of the industry in any conditions.